On the taxonomical and nomenclatural status of genus Orientalia Dang, 1975 (Crustacea: Decapoda: Brachyura: Potamidae) from Vietnam - Thanh, Dang Ngoc (Academia Journal of Biology, 2012)
Genus Orientalia Dang, 1975 was established by Dang Ngoc Thanh, based on type species Orientalia glabra Dang [= Potamon (Geothelphusa) glabra Dang, 1967] found in North Vietnam. Unfortunatly, the generic name Orientalia is considered as a junior homonym of the name Orientalia Radoman, 1972 (Mollusca). Yeo et al. (1998, 2005), Yeo & Naruse (2007) [8, 9, 10] has commented on this nomenclatural question, and suggested that the name Orientalia Dang, 1975 should be replaced by a junior subjective synonym Hainanpotamon Dai, 1995 established by Dai Ai-yun (1995) [1] based on the type species Hainanpotamon orientalis Parisi, 1916 (instead Hainanpotamon daiae sp. n., according to Yeo & Naruse (2007) [10]) found in Hainan Island. However, a detailed comparison on diagnostic morphological particularities of these two related genera, showed that they are not identical in the structure of male Gonopod 1 and carapace. Furthermore, the known species of the genus Orientalia Dang (O. glabra Dang, O. rubra Dang & Tran) are found in Vietnam - eastasian continental land - while the known species of Hainanpotamon Dai (H. daiae, H. helene, H. fuchengense) has an original island distribution in Hainan Island, isolated from Asian continental land since pleistocen period, that revealed 2 separated taxonomical speciation of these two different species groups. So that, in our opinion, it needs a further taxonomical study and discussion, in order to confirm the synonym relation of these two genera. For this reason, conforming to the Article 60 (60.3) of the IZNC, the author propose a substitute name Vietorientalia Dang, 2011, including a generic diagnosis, to replace the junior homonym name Orientalia Dang, 1975. Vietorientalia nom. n. Typ species: Potamon (Geothelphusa) glabra Dang, 1967. Dang Ngoc Thanh, 1967. Tap san Sinh vat - Dia hoc, VI(3-4): 155-165. Fig. 6. Diagnosis: Crab medium in size, carapace strongly convex, length is 3/4 broad, upper surface smooth or with silky specks, and with scarlet or yellowish colour. Regions of dorsal surface are distinctly distinguished by dotted lines. Anterofrontal margin with round angle bilobed or four-lobed. Postorbital tooth small, separated from epibranchial tooth by cleft. Anterolateral border with smally granulated cristae. The third maxilliped exopod with flagellum. Chelipeds unequal, right chela larger than left one. Male abdomen telson equilateral triangular, rounded top. Male Gonopod 1 slender, subterminal segment with distal part tapering, terminal segment pointed stick in shape, curved outward, dorsal with round top triangular or semicircular flap, started from the beginning of proximal part, extending half or about half of this segment.